Genomic epidemiology of group B streptococci spanning 10 years in an Irish maternity hospital, 2008–2017. Issue 1 (July 2021) - Meehan, Mary; Eogan, Maeve; McCallion, Naomi; Cunney, Robert; Bray, James E.; Jolley, Keith A.; Unitt, Anastasia; Maiden, Martin C.J.; Harrison, Odile B.; Drew, Richard J.
Highlights: Genomic epidemiological analysis of Group B streptococcal isolates was performed using the S. agalactiae PubMLST database. CgMLST discriminated isolates of the same sequence type and, identified known and suspected case clusters. Isolates of clonal complex (CC) 17, CC23 and CC19 were most common in infant, maternal and non-invasive cases, respectively. Erythromycin and clindamycin resistance was associated with CC1, CC19 and erm (B) and, increased over the study period. Genome sequence analysis using the gene-by-gene approach implemented on a public database will facilitate GBS surveillance. Summary: Objectives: The genomic epidemiology of group b streptococcal (GBS) isolates from the Rotunda maternity hospital, Dublin, 2008–2017, was investigated. Methods: Whole genome sequences of isolates (invasive, n = 114; non-invasive, n = 76) from infants and women were analysed using the PubMLST database (https://pubmlst.org/sagalactiae/). Results: Serotypes III (36%), Ia (18%), V (17%), II (11%) and Ib, (9%) and sequence types (ST) 17 (23%), ST-23 (14%), ST-1 (12%) and ST-19 (7%) were most common. Core genome MLST (cgMLST) differentiated isolates of the same ST, grouped STs into five lineages congruent with known clonal complexes and identified known mother-baby pairs and suspected linked infant cases. Clonal complex (CC) 17 accounted for 40% and 22% of infant and maternal invasive cases, respectively and 21% of non-invasive isolates. CC23 and CC19 were associated with maternal disease (30%) and carriage (24%), respectively. Erythromycin (26%) and clindamycin (18%) resistance increased over the study period and was associated with presence of the erm (B) gene (55%), CC1 (33%) and CC19 (24%). A multi-resistant integrative conjugative element incorporated in the PI-1 locus was detected in CC17, an ST-12 and ST-23 isolate confirming the global dissemination of this element. All isolates possessed one or more pilus islands. Genes encoding other potential protective proteins including Sip, C5a peptidase and Srr1 were present in 100%, 99.5% and 65.8% of isolates, respectively. The srr2 gene was unique to CC17. Conclusions: The PubMLST.org website provides a valuable framework for genomic GBS surveillance to inform on local and global GBS epidemiology, preventive and control measures.